Force-velocity profile changes with forearm wearable resistance during standing start sprinting. Issue 7 (8th August 2020) - Macadam, Paul; Mishra, Megna; Feser, Erin H.; Uthoff, Aaron M.; Cronin, John B.; Zois, James; Nagahara, Ryu; Tinwala, Farhan
Abstract : Horizontal force-velocity (F-V) profiling is a strategy to assess athletes' individual performance capabilities during sprinting. This study investigated the acute changes in F-V profiles during sprinting of fourteen collegiate male sprinters with a mean 100-m sprint time of 11.40 ± 0.39 s, from a split-stance starting position. The subjects sprinted 30-m with, and without, wearable resistance (WR) equivalent to 2% body mass, attached to their forearms. Sprinting time at 5, 10, 20, and 30-m was assessed using laser technology. External horizontal F-V relationships were calculated via velocity-time signals. Maximal theoretical velocity ( V 0 ), theoretical relative and absolute horizontal force ( F 0 ), and horizontal power ( P max ) were determined from the F-V relationship. Paired t-tests were used to determine statistical differences ( p ≤ 0.05) in variables across conditions with Cohen's d as effect sizes (ES) calculated to assess practical changes. Sprint times at 10-m and beyond were significantly increased (1.9–3.3%, p 0.01–0.03, ES 0.46–0.60) with WR compared to unloaded sprinting. The only significant change in F-V with the WR condition was found in relative P max system (−6.1%, p 0.01, ES 0.66). A small decrease was reported in V 0 (−1.0%, p 0.11, ES 0.27), with small to medium ES decreases reported in F 0 (−4.8% to −6.1%, p 0.07–0.21, ES 0.25-0.51) and P max (−4.3% to −4.6%, p 0.06–0.08, ES 0.32–0.45). The greater changes to F 0 and P max suggest that forearm WR may be a possible training tool for athletes who wish to focus on force and power adaptation during sprint acceleration from a standing start.